Film and television adaptation: a comparative analysis of a streetcar named desire adaptations for cinema and television - Felix, José Carlos (2004)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente